Pos Pelayanan Teknologi: Masih Perlukah Dibentuk Guna Mendorong Pemberdayaan Masyarakat Desa. - Budhi Prabowo (LAP4B, 2025)
Technology Service Post (Posyantek) is one of the Indonesian government's strategic programs which aims to empower the community through the application of appropriate technology (TTG). Posyantek functions as a center for information, consultation and technology training that can be accessed by the community at the village and sub-district levels. This program is designed to support local economic development, increase productivity, and strengthen community competitiveness through technological solutions that suit local needs. The establishment of Posyantek was based on the need to bridge the technology gap between rural and urban areas. The method for writing this literature review is library study, where the author obtains information from textbooks, articles, modules or the internet. Examining theories and relationships or influences between variables from online books and journals sourced from Mendeley, Google Scholar and other online media. Technology Service Posts (Posyantek) are still very relevant to be established and maintained at this time, especially with the challenges and opportunities faced by society in the digital era and increasingly developing technology.